Student's pocket companion to accompany Physics - Cutnell, John D. (Wiley, 1998)
Describes applications in medicine, automobile features, transportation, home entertainment, athletics, household applications, information processing, detection devices, camera technology, and many more. Contains numerous discussions and examples that focus on human physiology, including muscle forces, blood pressure, the refraction of light by the eye, and many others.